2020
DOI: 10.1186/s12893-020-00847-z
|View full text |Cite
|
Sign up to set email alerts
|

Bridge to surgery using a self-expandable metallic stent for stages II–III obstructive colorectal cancer

Abstract: Background: Bridge to surgery (BTS) using a self-expandable metallic stent (SEMS) for the treatment of obstructive colorectal cancer improves the patient's quality of life. This study aimed to examine prognostic factors of obstructive colorectal cancer. Methods: We analyzed stage II-III resectable colon cancer cases (Cur A) retrospectively registered between January 2005 and December 2017. Overall, 117 patients with Cur A obstructive colorectal cancer were evaluated: 67 of them underwent emergency surgery (ES … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…As SEMS mechanically dilates the lumen in OCRC, there are concerns regarding the dissemination of tumors into the peritoneal cavity [28], invasion of tumor cells into the venous [29] and lymphatic vessels [30], and perineural invasion [31]. However, according to histopathological examinations conducted in previous studies, these factors were not exacerbated by SEMS placement [13,24]; this is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…As SEMS mechanically dilates the lumen in OCRC, there are concerns regarding the dissemination of tumors into the peritoneal cavity [28], invasion of tumor cells into the venous [29] and lymphatic vessels [30], and perineural invasion [31]. However, according to histopathological examinations conducted in previous studies, these factors were not exacerbated by SEMS placement [13,24]; this is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Sabbagh et al reported that in left-sided obstructive colorectal cancer, post-stent insertion surgery had a poorer long-term prognosis, with more tumor and peritumoral ulceration, perineural invasion, and lymph node metastasis 10,12) . Ohta et al reported that surgical cases after stent insertion had higher rates of lymph node metastasis and venous invasion and poorer 3-year OS than emergency resection 11) . Meta-analyses of RCTs by Foo et al and Yang et al reported no difference regarding survival, but a higher recurrence rate was observed in left-sided obstructive colorectal cancer 7,8) .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is no consensus on the long-term prognosis. There are reports of stent insertion adversely affecting pathological findings such as lymph node metastases, vascular invasion, and nerve invasion 10,11) , as well as poor long-term prognosis 11,12) . A 46-center prospective study in Japan reported a high success rate of stent insertion with favorable long-term prognosis 13) .…”
Section: Introductionmentioning
confidence: 99%
“…In a comparative study between emergency surgery and BTS using SEMS, age, performance status, depth of invasion, and lymph node metastasis were prognostic factors for disease-free survival [ 27 ]. A Japanese study of 50 cases of emergency surgery and 50 cases of BTS using SEMS for Stage II/III obstructive CRC showed that BTS and positive venous invasion were poor prognostic factors for RFS, and BTS and T4 cancer were poor prognostic factors for overall survival (OS) [ 28 ]. Long-term outcomes (OS and disease-free survival [DFS]) of emergency surgery and BTS using SEMS were equivalent, but NLR was a prognostic factor for DFS in emergency surgery.…”
Section: Discussionmentioning
confidence: 99%